A Survey Paper: Implementation of the Internet of Things in Industry - Andi Kurniawan (ITEJ (Information Technology Engineering Journals), 2020)
The use of the Internet of Things (IoT) has been widely developed in various fields of technology application. Using IoT can make it easier to build robust industrial systems and applications and provide visualization for the safety of industrial employees by taking advantage of the increasing number of radio frequencies, wireless devices, mobile devices and sensors. In understanding the development of IoT in the industry, the paper reviews the latest IoT research, a survey that compares the use of IoT from several existing papers, the main applications of IoT in the industry, and identifies trends and research challenges. The main contribution of this survey paper is to systematically summarize the current state of IoT in the industry.